Carbon felt/nitrogen-doped graphene/paraffin wax 3D skeleton regulated tribological performances of the MCPA6 composites: A novel strategy of oil embedding and transporting. (June 2023) - Liu, Hongyu; Wang, Zhou; Pan, Bingli; Li, Menghan; Huang, Saisai; Lee, Joong Hee; Kim, Nam Hoon
Abstract: A novel carbon felt/nitrogen-doped reduced graphene oxide/paraffin wax ternary skeleton (CF/N−RGO/PW) is developed to enhance the tribological performances of monomer casting nylon-6 (MCPA6). FE−SEM results confirm the successful formation of the three-dimensional (3D) CF/N−RGO/PW skeleton, where N−RGO sheets are decorated on carbon fibers. Most importantly, the flexuous N−RGO sheets can accommodate PW to provide sufficient lubricity for MCPA6, working as ponds to store PW. On the other hand, abundant cracks are found along carbon fibers, working as ditches to transport PW onto the rubbing surface. Thus, the ternary CF/N−RGO/PW 3D skeleton exhibits a pond and ditch structure for the efficient storage and transportation of PW. In comparison with the neat MCPA6, the friction coefficient and wear loss of MCPA6/CF/N−RGO/PW decline by (83 and 65) %, respectively. Theoretical calculations based on density functional theory support the efficient adsorption of PW onto N−RGO. Therefore, the as-prepared MCPA6/CF/N−RGO/PW composite herein provides a new reference to prepare polymer composites with advanced tribological performance on account of the novel strategy of the storage and transportation of lubricants. Graphical Abstract: ga1 Highlights: A novel CF/N-RGO/PW ternary skeleton was developed for advanced tribological performances of MCPA6. The ternary skeleton exhibits a unique ponds and ditches structure. The excellent tribological performances were attributed to the efficient storage and transport of PW. Theorotical calculation comfirmed the adsorption of PW by N-RGO sheets.